Primary leiomyoma of the pulmonary vein. Issue 5 (May 1992) - Peters, P; Trotter, S E; Sheppard, M N; Goldstraw, P
Abstract : The first case of a primary leiomyoma in a pulmonary vein in an adult is presented. Although rare, leiomyoma and leiomyosarcoma of the lung and great vessels should be included in the differential diagnosis of intrathoracic space occupying lesions.